Customer Satisfaction and Loyalty: The Role of Interaction and Neuromarketing - Barrientos-Báez, Almudena; Carvajal Zaera, Enrique; Caldevilla-Domínguez, David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study explores the relationship between customer satisfaction and loyalty within retail formats, analysing the key variables that influence consumer behaviour and the contribution of neuromarketing tools. Employing a qualitative research approach, a focus group comprising experts in distribution and customer loyalty revealed that satisfaction with interaction is the most significant factor, followed by satisfaction with outcomes and satisfaction with the environment. The study also identifies the impact of store format on loyalty, demonstrating that neighbourhood shops foster greater loyalty due to personalised service. These findings enhance the understanding of consumer preferences, underscoring the critical role of customer interaction in retail strategies.